Thermal imaging is a non-invasive alternative to PET-CT for measurement of brown adipose tissue activity in humans - Law, James; Morris, David E.; Izzi Engbeaya, Chioma; Salem, Victoria; Coello, Christopher; Robinson, Lindsay J.; Jayasinghe, Maduka; Scott, Rebecca; Gunn, Roger; Rabiner, Eugenii; Tan, Tricia; Dhillo, Waljit S.; et al. (Society of Nuclear Medicine, 2018)
Background Obesity and its metabolic consequences are a major cause of morbidity and mortality. Brown adipose tissue (BAT) utilises glucose and free fatty acids to produce heat, thereby increasing energy expenditure. Effective evaluation of human BAT stimulators is constrained by current standard BAT assessment methods as positron emission tomography-computed tomography (PET-CT) requires exposure to high doses of ionising radiation. Infrared thermography (IRT) is a potential non-invasive, safe alternative, although direct corroboration with PET-CT has not previously been established. Methods IRT and 18F-fluorodeoxyglucose (¹⁸F-FDG) PET-CT data from 8 healthy male participants subjected to water jacket cooling were directly compared. Thermal images (TIs) were geometrically transformed to overlay PET-CT-derived maximum intensity projection (MIP) images from each subject and the areas of greatest intensity of temperature and glucose-uptake within the supraclavicular regions compared. Relationships between supraclavicular temperatures from IRT (TSCR) and the maximum rate of glucose uptake (MR(gluc)) from PET-CT were determined. Results Glucose uptake on MR(gluc)MIP was positively correlated with change in TSCR relative to a reference region (r² = 0.721; p=0.008). Spatial overlap between areas of maximal MR(gluc)MIP and maximal TSCR was 29.5±5.1%. Prolonged cooling to 60 minutes was associated with further TSCR rise compared with cooling to 10 minutes. Conclusions The supraclavicular hotspot identified on IRT closely corresponds to the area of maximal uptake on PET-CT-derived MR(gluc)MIP images. Greater increases in relative TSCR were associated with raised glucose uptake. IRT should now be considered a suitable method for measuring BAT activation, especially in populations where PET-CT is not feasible, practical or repeatable.